Scaling in charged fluids: beyond simple ions - Blum, L. (Condensed Matter Physics, 2001)
The analytical solution of the Mean Spherical Approximation for a quite general class of interactions is always a function of a reduced set of scaling matrices Γχ. We extend this result to systems with multipolar interactions: We show that for the ion-dipole mixture the thermodynamic excess functions are a functional of this matrix. The result for the entropy is S = −{kV/3π}(F[Γα])α∈χ where F is an algebraic functional of the scaling matrices of irreducible representations χ of the closure of the OrnsteinZernike. The result is also true for arbitrary electrostatic multipolar interactions. Аналітичний розв’язок середньосферичного наближення для достатньо загального класу взаємодій є завжди функцією редукованого набору скейлінгових матриць. Ми розширюємо цей результат на випадок систем з мультипольними взаємодіями. Ми показуємо, що для іонно-дипольної суміші термодинамічні надлишкові функції є функціями цієї матриці. Результат для ентропії є S = −{kV /3π}(F[Γα])α∈χ, де F – алгебраїчний функціонал скейлінгових матриць незвідних представлень замикання Орнштейна-Церніке. Результат дійсний також і для довільних електростатичних мультипольних взаємодій.